Reducing Coronary Heart Disease Risk Through Treatment of Insomnia Using Web-Based Cognitive Behavioral Therapy for Insomnia: A Methodological Approach. Issue 3 (3rd May 2020) - Javaheri, Sogol; Reid, Michelle; Drerup, Michelle; Mehra, Reena; Redline, Susan
ABSTRACT: Objective : Observational data demonstrate increased risk of recurrent acute coronary syndrome in patients with comorbid insomnia. We conducted a pragmatic randomized controlled pilot study to address knowledge gaps and inform future large-scale randomized trials to test the impact of Web-based cognitive behavioral therapy for insomnia (wCBT-I) on coronary heart disease (CHD) outcomes. Participants : Thirty-five adults recruited from Brigham and Women's and Cleveland Clinic Hospitals with insomnia, defined by Insomnia Severity Index (ISI) score ≥ 10 and symptoms of at least 3 months, and comorbid CHD identified from medical records. Methods : We randomized 34 patients to either general sleep education coupled with wCBT-I or general sleep education alone followed by an opportunity for treatment after the study (a wait-list control) to evaluate feasibility and uptake of insomnia treatment in patients with heart disease. Participants completed the ISI at baseline and 6 weeks to assess insomnia severity. Results : Twenty-nine adults completed the trial, yielding an 85% retention rate, and adherence rate in the treatment arm was 80%. Mean age was 71.6 ± 9.5 years, 75% were male, and mean body mass index (BMI) was 29 ± 4.5 kg/m 2 . Baseline ISI scores were 15.6. There was a 6.2 ± 5.3 point reduction in ISI scores in the intervention arm and a 3.3 ± 5.1 reduction in the control arm ( p value 0.1). Conclusion : Web-based CBT-I intervention was feasible in an older sample with prevalent CHD and resulted in clinically meaningful improvement in insomnia severity, though statistical significance was limited by lack of power.